Distribusi Vertikal Diatom Epipelik di Muara Sungai Banjir Kanal Timur Semarang - Edwin Nurimansyah; Tri Retnaningsih Soeprobowati; M Murningsih (Jurnal Akademika Biologi, 2015)
Diatom is microalgae that has a wide distribution and cosmopolite. Diatom can be used as bioindicator of environment changes in the past, because of its sensitivity to habitat condition and its characteristic which can be fossilize. This research was conducted in Muara Sungai Banjir Kanal Timur Semarang. This location selected on the tide area. This reasearch aims to assess the abundance, diversity, and equal distribution of fossils diatom The research begins by taking samples of sediment to a depth of 34 cm and then sliced per-6 cm.The result was found 36 species diatom, the most abundant species is Pinnularia borealis Ehrenberg. Diversity index between 1.84 – 2,58 shows that the ecosystem in Muara Sungai Banjir Kanal Timur Semarang has environmental conditions are less stable until rather stable based its benthic diatom communities. Distribution the individuals number of each species evenly distributed on each layer. The dominance of diatom was found are Pinnularia (Pinnularia biceps, Pinnularia rabenhorstii, Pinnularia borealis), it’s dominance in each layer. Keywords: bioindikator, diatom, muara Sungai Banjir Kanal Timur Semarang.